2011
DOI: 10.1144/sp351.7
|View full text |Cite
|
Sign up to set email alerts
|

Palaeostress analysis of a giant Holocene rockslide near Boaco and Santa Lucia (Nicaragua, Central America)

Abstract: A giant rockslide occurred on the southern side of an Upper Tertiary shield volcano in central Nicaragua in the Holocene. The failure caused tectonic-like deformation of rock masses and changed the local stress regime. The lower, compressional part of the rockslide produced a stress field with the axis of maximum stress (σ1) parallel to the displacement vector of the main body. The upper part of the rockslide was gravity-driven with σ1 vertical and σ3 horizontal, and oriented SE–NW. The mass tended to move SE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In a volcanic setting it has been found that slow collapse of a Tertiary shield volcano in the Nicaraguan Highlands during the Holocene modified the local palaeostress field and generated normal, reverse, and strike slip faults (Baroň et al, 2011). However, volcanic collapses are somewhat difficult to study because they are comparatively rare events.…”
Section: Introductionmentioning
confidence: 99%
“…In a volcanic setting it has been found that slow collapse of a Tertiary shield volcano in the Nicaraguan Highlands during the Holocene modified the local palaeostress field and generated normal, reverse, and strike slip faults (Baroň et al, 2011). However, volcanic collapses are somewhat difficult to study because they are comparatively rare events.…”
Section: Introductionmentioning
confidence: 99%